The Impact of Digital Economy on Emerging Markets: A Review of Trends and Challenges - Vij, Suman (AG Volumes, 2025)
The digital economy has emerged as a progressive economy that employs electronic communication and digital technologies to conduct economic and business operations in a diverse array of sectors, such as digital marketing, e-commerce, software development, digital financial services, cloud services and computer games. This article reviews the body of research on the trends and difficulties associated with the digital economy's impact on developing economies. This review highlight that the digital economy significantly influences emerging markets by driving economic growth through e-commerce, ICT infrastructure, and digital innovation. While offering vast opportunities across sectors like healthcare, education, and governance, it also presents challenges such as data privacy, cybersecurity, and workforce displacement due to AI. Strategic investments in ICT, targeted regulatory frameworks, and comprehensive training programs are essential to harness these benefits. Encouraging digital adoption and enhancing human capital will reduce regional disparities and foster inclusive economic development. With focused efforts, emerging markets like Indonesia can leverage digital transformation to ensure sustainable growth and competitiveness in the global digital landscape.